Clinicopathological features affecting the establishment of patient-derived xenograft models of colorectal cancer - Li Wenxin; Zhang Zihan; Chen Zhongyang; Lin Yirong; Wang Yulong; Chen Dawei; Zhang Sen (结直肠肛门外科)
[Objectives] To determine the clinicopathological features affecting the establishment of patient-derived xenograft (PDX) models of colorectal cancer. [Methods] Tumor tissues and clinicopathological features of 119 patients with colorectal cancer treated surgically at the Department of Colorectal & Anal Surgery, The First Affiliated Hospital of Guangxi Medical University, were collected between April and August 2021. PDX models of colorectal cancer were established and divided into the success group and failed group. Clinicopathological features affecting the establishment of PDX models of colon and rectal cancer were analyzed separately. Potential clinicopathological features include age, sex, coexisting chronic conditions, location of the tumor, the proportion of intestinal cavity occupied by the tumor, maximum tumor diameter, preoperative CEA level, preoperative CA199 level, preoperative CA125 level, metastasis, general tumor classification, histological classification, depth of invasion, lymph node metastasis, nerve invasion, vascular invasion, and Ki-67 index. [Results] Of all the patients, 81 had colon cancer, and 38 had rectal cancer. PDX models were successfully established in 31 cases of colon cancer and 13 cases of rectal cancer. For colon cancer, the success group and failed group differed significantly in terms of maximum tumor diameter and metastasis in patients (P < 0.05). For rectal cancer, the success group and failed group differed significantly in terms of nerve invasion and metastasis in patients (P < 0.05). [Conclusion] Patients have metastasis or not is associated with the establishment of PDX models of colorectal cancer. Maximum tumor diameter and nerve invasion of patients were associated with the outcome of the establishment of PDX models of colon cancer and rectal cancer, respectively.